Optimization of Combinational Logic Circuits with Genetic Programming - Karakatic, S.; Podgorelec, V.; Hericko, M. (Elektronika ir Elektrotechnika, 2013)
In this paper we research the possibility of automated combinational logic circuit (CLC) design using evolutionary computation. We propose and develop a genetic programming method which is able to construct a CLC based on the given truth tables, where the focus is to minimize the number of logic gates while accuracy is not compromised. We tested the proposed approach and compared the results both with MGA and NGA automatic methods as well as with the results obtained by human designers. Results show that our algorithm is superior to other methods as it can find correct circuits with fewer specified elements. The experiments performed on larger examples show good performance and scalability of the proposed evolutionary approach. DOI: http://dx.doi.org/10.5755/j01.eee.19.7.5169